1998
DOI: 10.1007/s004410051139
|View full text |Cite
|
Sign up to set email alerts
|

Age-related nephropathy in the Fischer 344 rat is associated with overexpression of collagens and collagen-binding heat shock protein 47

Abstract: To explore the possible role of heat shock protein (HSP) 47 in the age-related renal changes in Fischer 344 (F 344) rats, the expression of collagen-binding HSP47 with various proteins implicated in phenotypic modulation (alpha-smooth muscle actin, desmin, and vimentin) and fibrosis (type I, type III, and type IV collagens) was examined in young and old F 344 rat kidneys. Male F 344 rats often develop spontaneous nephropathy in old age. Kidneys obtained from 24-month-old F 344 rats showed glomerulosclerosis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
(22 reference statements)
2
42
0
Order By: Relevance
“…For example, the HSP47 expression was augmented in CCl 4 -induced liver cirrhosis, bleomycin-induced pulmonary fibrosis and antithymocyte serum induced glomerulosclerosis in rats in parallel with increased deposition of various collagens [12, 16, 22]. The expression of HSP47 was also markedly elevated in gentamicin nephropathy, hypertensive Dahl rat kidneys, cisplatin-induced tubulointerstitial nephritis and aging Fischer 344 rat kidneys in parallel with increased expression of various collagens [13, 23, 24, 25]. From the collagen-synthesizing ability, it is thought that increased levels of HSP47 in human DN and IgAN might have a key regulatory role for sclerotic/fibrotic changes that are found in the advanced stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the HSP47 expression was augmented in CCl 4 -induced liver cirrhosis, bleomycin-induced pulmonary fibrosis and antithymocyte serum induced glomerulosclerosis in rats in parallel with increased deposition of various collagens [12, 16, 22]. The expression of HSP47 was also markedly elevated in gentamicin nephropathy, hypertensive Dahl rat kidneys, cisplatin-induced tubulointerstitial nephritis and aging Fischer 344 rat kidneys in parallel with increased expression of various collagens [13, 23, 24, 25]. From the collagen-synthesizing ability, it is thought that increased levels of HSP47 in human DN and IgAN might have a key regulatory role for sclerotic/fibrotic changes that are found in the advanced stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This was performed to localize HSP47/CD68, HSP47/α-smooth muscle actin, HSP47/type III collagen and HSP47/type IV collagen in the same renal section as described earlier [12, 13]. Briefly, selected paraffin sections (4 µm) were deparaffinized, treated with 0.3% hydrogen peroxide in methanol (30 min), reacted with 10% nonimmune goat serum (10 min) and incubated with monoclonal antibody against HSP47 for 1 h. The sections were further treated with biotinylated second antibody (10 min) and streptavidin-alkaline phosphatase (10 min) and developed with BCIP/NBT which produce a dark-purple stain.…”
Section: Methodsmentioning
confidence: 99%
“…64 Research in rodents has provided further support for the roles of insulin-like growth factor 1 and heat shock proteins. 62,85 GS in humans was associated with upregulation of cell-cycle regulators p16…”
Section: Molecular Mechanisms Of Renal Agingmentioning
confidence: 99%
“…Earlier studies have convincingly shown that increased synthesis of collagens by interstitial myofibroblasts and tubular epithelial cells results in tubulointerstitial fibrosis. In rat models, an increased expression of HSP47 was consistently observed in the interstitial myofibroblasts and tubular epithelial cells during the process of experimental and spontaneous tubulointerstitial fibrosis [14, 15, 16]. Increased expression of HSP47 was seen in and around areas of interstitial fibrosis, and it colocalizes with collagens (types I and III).…”
Section: Hsp47 and The Kidneymentioning
confidence: 99%